Bayesian assessment of an existing bridge: a case study - Jacinto, Luciano (2017)
Nowadays, companies in global markets have to achieve high levels of performance and competitiveness to stay "alive”. Within this assumption, the building maintenance cannot be done in a casual and improvised way due to the costs related. Starting with some discussion about lean management and building maintenance, this paper introduces a model to support the Lean Building Maintenance (LBM) approach. Finally based on a real case study from a Portuguese company, the benefits, challenges and difficulties are presented and discussed.